Uṣūl al-Fiqh Literacy for the Local Community: A Study on Shaykh Mukhtar Ambai’s Manuscript - Repelita, Repelita; Iskandar, Nuzul; Mursal, Mursal (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Ancient manuscripts with uṣūl al-fiqh themes remain rare amidst the increasing efforts to inventory, categorize, and digitize old manuscripts in present-day Indonesia. Nevertheless, literacy initiatives related to uṣūl al-fiqh can still be identified within manuscripts exploring different subjects. This study aims to elucidate how a non-uṣūl al-fiqh-themed manuscript can encompass uṣūl al-fiqh insights intended for a local community. Employing a documentary approach, it relies on primary data from Risālah Marḍiyah by Shaykh Mukhtar Ambai Kerinci. Subsequently, content analysis utilizing a qualitative model captures messages, meanings, linguistic styles, and symbolic interactions. The study reveals that uṣūl al-fiqh’s topics in the manuscript are conveyed using five methods: illustration and exemplification, the statement-argument-example pattern, comparison, argumentative conjunction, if-then pattern, and citation models. The argument posits that scholarly uṣūl al-fiqh literacy efforts in the past need not be solely assessed by the quantity of ancient uṣūl al-fiqh-themed manuscripts; instead, they can be discerned in other manuscripts employing more operationally creative, contextual, and easily comprehensible delivery methods, serving a broader audience.